2022
DOI: 10.3390/cancers14051348
|View full text |Cite
|
Sign up to set email alerts
|

Testing for Lynch Syndrome in Endometrial Carcinoma: From Universal to Age-Selective MLH1 Methylation Analysis

Abstract: International guidelines recommend universal screening of endometrial carcinoma (EC) patients for Lynch syndrome (LS). This screening is generally based on mismatch repair (MMR) protein immunohistochemistry followed by MLH1 methylation analysis of MLH1-negative cases to exclude the likely sporadic cases from germline testing. As LS-associated EC is uncommon in the elderly, age-selective methylation testing could improve cost-efficiency. We performed MMR immunohistochemistry on 821 unselected ECs (clinic-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Mismatch repair deficiency has been linked to MSI, which is a hallmark of Lynch syndrome, a hereditary cancer syndrome that predisposes individuals to various malignancies, including endometrial carcinoma. 14 However, in sporadic endometrial carcinoma, MMR deficiency can occur through somatic mutations or epigenetic silencing of MMR genes. 15 The detection of MMR deficiency by immunohistochemical staining has important implications for the diagnosis, classification, and management of endometrial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Mismatch repair deficiency has been linked to MSI, which is a hallmark of Lynch syndrome, a hereditary cancer syndrome that predisposes individuals to various malignancies, including endometrial carcinoma. 14 However, in sporadic endometrial carcinoma, MMR deficiency can occur through somatic mutations or epigenetic silencing of MMR genes. 15 The detection of MMR deficiency by immunohistochemical staining has important implications for the diagnosis, classification, and management of endometrial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies showed that some MSI EC cases also harbouring other mutations overlapped with different molecular phenotypes, the TCGA classified MSI EC as a distinct molecular phenotype [ 124 ]. LS in the EC was observed with a frequency of 3% [ 125 ].…”
Section: Msi In Gynecologic Cancersmentioning
confidence: 99%
“…Assuming that women with both endometrial cancer and LS are typically younger than women with endometrial cancer but without LS, Pasanen et al [4] tested whether limiting MLH1 methylation analysis to women below a certain age threshold could improve the cost-benefit ratio compared to the proposed age-independent universal screening. They tested tumor tissue samples from 842 women who underwent surgery at the Helsinki University Hospital over 5 years and from 142 women who were included in the Finnish national registry of LS patients.…”
mentioning
confidence: 99%
“…If the MLH1 methylation analysis had been limited to women under 65 years, this would have excluded almost 71% of women from the analysis. If the MLH1 methylation analysis had been limited to women under 70 years, this would have excluded just over 56% of women from the analysis [4]. Considering an age threshold of 60 years, the sensitivity of the method would have been 50% for the hospitalbased cohort and 88.6% for the registry-based cohort.…”
mentioning
confidence: 99%
See 1 more Smart Citation